The Legal Certainty Of Waarmerking In Notarized Sale And Purchase Agreements: A Case Analysis Of Civil Proceedings (Case Research: District Court Decision No. 354/PDT.G/2019/PN.SDA) - Ayu Tika Sari, Lavrida; Taruno Muryanto, Yudho; Sri Ciptorukmi, Anjar (International Journal of Educational Research & Social Sciences, 2024)
The purpose of this research is to determine The Legal Certainty of Waarmerking in Notarized Sale and Purchase Agreements: A Case Analysis of Civil Proceedings (Case research: District Court Decision No. 354/Pdt.G/2019/PN.Sda). The research employed in this research is normative research, drawing from literature studies. Data collection techniques involve an extensive literature review. The outcomes indicate that a waarmerking agreement possesses robust legal evidentiary authority in civil cases, contingent upon the parties acknowledging the signatures within the agreement. This is attributed to the fact that the function of waarmerking deeds under the hand primarily ensures the accuracy of the date in the registration of deeds under the hand in a dedicated book within the notary office. In the Sidoarjo court decision, the waarmerking of the binding agreement of sale and purchase, once waarmerked, is deemed valid and binding for both parties by the judge. However, it is noteworthy that the binding agreement of sale and purchase, serving as the foundation for the lawsuit, fails to meet the essential criteria for a valid agreement concerning the specification of "a certain thing." The subject matter pledged in the agreement has undergone a transfer of ownership to a different entity. Consequently, the binding agreement of sale and purchase in the Sidoarjo Court's civil cases lacks legal evidentiary force, as it is deemed to fall short of meeting the essential requisites of the agreement. This situation introduces legal uncertainty for other parties currently exercising control over the land and building.